Using citizen science to understand and map habitat suitability for a synurbic mammal in an urban landscape: the hedgehog Erinaceus europaeus. (14th December 2021) - Turner, Jessica; Freeman, Robin; Carbone, Chris
Abstract: Urban environments are important for west European hedgehogs Erinaceus europaeus . The species has been recorded in 73% of large urban areas throughout its geographic range. However, the environmental relationships determining hedgehog distribution within these landscapes are not well understood. Taking a city‐wide perspective, this study identifies hedgehogs' habitat relationships with urban environmental characteristics and predicts habitat suitability in a major urban centre, Greater London, UK. We use a collated citizen science dataset of 3012 hedgehog occurrence records from Greater London, and pseudoabsences inferred from other mammal taxa, to construct a multiscale generalised linear model identifying the influence of 10 variables representing urban greenspace, built infrastructure, and the presence of the European badger Meles meles (as a predator or competitor) on hedgehog distribution. We find a positive association of hedgehog presence with availability of gardens, parks, allotments, percentage of terraced housing, traffic, and intermediate impervious cover (roads and buildings, peaking at 31%). High impervious cover, woodland, water, human densities (above 2262 people km −2 ), and badger presence were negatively related to hedgehog presence. Predicted habitat suitability was high across much of Greater London but declined towards the centre and in some locations around the outskirts of the study region. Our results emphasise the importance of public and private greenspaces for urban hedgehogs, and suggest that loss of garden, park, and allotment habitats and disturbance associated with high human densities may restrict hedgehog distribution. Despite the inherent complexity of urban environments, this study shows that citizen science is useful for developing an understanding of large‐scale species–habitat relationships in diverse urban landscapes. Abstract : We used citizen science to understand and map habitat suitability for the hedgehog Erinaceus europaeus, a synurbic mammal, in the urban landscape of London, UK. A map of predicted habitat suitability for hedgehogs across Greater London was obtained by relating citizen science observations of hedgehogs to environmental characteristics such as gardens, open greenspaces, human density, and presence of predators. Public and private greenspaces are important for hedgehogs, and high human densities and badger presence are negatively related to hedgehog presence.